Era of covid-19: How the pandemic affected gender inequality and fertility (on the example of BRICS) - E. A. Mosakova (RUDN journal of Sociology, 2023)
One of the most important tasks on the way to the global sustainable development in the 21st century is gender equality. The article considers one aspect of this task - achieving more complete gender equality in the labor market by providing women with additional opportunities to combine professional and family responsibilities. The covid-19 pandemic contributed to gender equality in the labor market and to the growth of birth rate. On the one hand, digitalization and remote forms of employment allow women to better combine family and professional activities. On the other hand, for employers, the gender of the employee is becoming less significant. However, the impact of the pandemic on gender equality depends on the structure of the economy. Thus, in countries with a higher share or a more developed tertiary sector, remote forms of employment develop faster, which contributes to gender equality in the labor market. On the example of the BRICS countries the author shows some dependencies between gender inequality in economy and education, female employment and birth rate. Thus, in the BRICS countries with expanded and narrowed reproduction, a higher level of gender equality in economy corresponds to a higher level of fertility and a higher mean age of women at the birth of the first child. All BRICS countries show the direct relationship between birth rate and female employment: a higher level of female employment corresponds to a higher level of birth rate, and vice versa.